Real-World Emission Assessment of Diesel Passenger Cars in Urban Traffic: A Comparative Analysis of Compliance with Bharat Stage VI Standards - Meena, Sanu; Singh, Suresh Kumar (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Urban air pollution, significantly influenced by vehicle emissions, poses severe health risks, particularly in rapidly urbanizing cities. This study investigates real-world emissions from diesel-powered passenger cars under mixed traffic conditions, focusing on compliance with Bharat Stage VI (BS VI) standards. Using Portable Emission Measurement Systems (PEMS), emission factors for Carbon Monoxide (CO), Oxides of Nitrogen (NOx), and the combined mass of Hydrocarbons and Oxides of Nitrogen (THC + NOx) were measured. Results revealed exceedances of 75%, 103.75%, and 40.59% for CO, NOx, and THC + NOx, respectively, underscoring inefficiencies in emission control technologies. Variability in emissions was linked to vehicle age, maintenance, driving behaviors, and challenging road conditions. These findings highlight the critical gap between laboratory-tested and real-world emissions, emphasizing the need for stricter regulations, advanced emission technologies, and public awareness campaigns. The study offers actionable insights for urban air quality improvement and policy development to reduce vehicular pollution.